Retrospective Cohort Study on Effect of Frenulotomy Techniques on Breastfeeding - Chompoonoot Boonsopa; Yasinee Apiraknapanon (Siriraj Medical Journal, 2020)
Objective: The aim of this study was to compare the outcomes between frenulotomy by bedside technique and surgery under general anesthesia to successful breastfeeding in ankyloglossia infants. Methods: A quantitative research of retrospective cohort study was conducted in Naresuan University Hospital, Thailand between July 2012 and June 2017. We enrolled all infants born and identified the infants diagnosed with ankyloglossia. The severity of ankyloglossia was assessed. The outcome of two types of frenulotomy were compared. Results: Ankyloglossia was diagnosed in 187 (6.3%) of 2,968 infants born. The main breastfeeding problems in both groups were maternal sore nipples, cracked nipples and poor latch on. The infants in the bedside technique group had more successful rate of exclusive breastfeeding at day 7 when compared with the surgical group (87.3% and 39% respectively, p<0.001). More percent increment of infant’s body weight at day 7 in the bedside technique group than the surgical group (60% and 20.8% respectively, p<0.001). Overall maternal satisfaction in the bedside technique group was notably higher than that in the surgical group (96.4% and 59.7% respectively, p< 0.001). The length of hospital stay was less in the bedside group for 1.22 days. More weight gain was found in the bedside group. Conclusion: Frenulotomy is the procedure that should be performed in indicated ankyloglossia infants. The bedside technique frenulotomy is preferable than surgery under general anesthesia attributed to a more satisfactory outcome.